Enhancing Physiological Quality of Aged Pak Choi (Brassica rapa L.) Seeds Through Different Invigoration Methods - Sarah Sakinah Umadi; Adhitya Vishnu Pradana (Jurnal Ilmu Pertanian, 2026)
Seed deterioration during storage significantly reduces the viability and productivity of pak choi (Brassica rapa L.). This study aimed to evaluate the efficacy of various synthetic and bio-organic invigoration agents combined with different soaking durations to restore the physiological quality of aged seeds (initial germination of 31%). The experiment was arranged in a factorial split-plot design. The main plots consisted of seven invigorating solvents: water (S1), shallot extract 50% (S2), mung bean sprout extract 5% (S3), bamboo shoot extract (S4), KNO₃ 1% (S5), GA₃ 100 ppm (S6), and PEG 6000 10% (S7). The sub-plots were three soaking durations: 15 (V1), 30 (V2), and 60 minutes (V3). The results indicated that a 30-minute soaking duration (V2) provided the optimal physiological window for metabolic repair without compromising desiccation tolerance. 10% PEG 6000 and 50% shallot extract emerged as the superior activators, consistently yielding the highest germination rates (up to 95.11%) and vigor indices (97.33%). While 10% PEG 6000 optimized post-emergence biomass, 50% shallot extract acted as a potent biostimulant due to its endogenous phytohormones. Furthermore, Radicle Emergence (RE) testing at 22 hours was identified as the most accurate diagnostic tool for predicting final germination capacity, particularly for the 30-minute treatment (R2 = 0.9943). Conversely, bamboo shoot extract (S4) exhibited a strong inhibitory effect, likely due to allelopathic phenolic compounds, and is not recommended for invigoration. In conclusion, hydropriming or shallot extract treatment for 30 minutes offers a practical and effective strategy for rehabilitating aged pak choi seeds.